Determinants of economic performance of environmental technology-based offers: a cross-sectional study of small Swedish firms. (2016) - Linder, Marcus
The paper examines the association between offer differentiation based on environmental orientation and economic performance. The analysis consists of an ordinary least-squares regression based on accounting data and a survey of the leaders of small environmental technology-based firms in Sweden. The results indicate that eco-efficiency creating a low total cost of ownership is more strongly associated with offer performance than is regulatory support, eco-branding, eco-quality differentiation and provision of strategic environmental information. This suggests that environmental differentiation of offers is the most successful when it is associated with a low total cost of ownership for customers.